Reconstruction of maxilla alveolus for application of dental implant in patients with cleft defect - Dušková, Markéta; Koťová, Magdalena; Urban, František; Sosna, Bohumil; Jirkalová, Radana; Strnadel, Tomáš; Kristen, Michal; Leamerová, E; Gojiš, O (Acta chirurgiae plasticae (English ed.), 2004)
The prospective study of dental implant application into the reconstructed maxilla alveolus of cleft patients was started in 2001. Its aims are to specify precisely the indications, conditions and techniques, as well as the factors justifying the assumption that the results will be successful. Indication was based on an examination by a multidisciplinary therapeutic team (plastic surgeon, dental surgeon, orthodontist, and prosthetist), with the proviso that the patient should have a positive approach. Successful orthodontic treatment of intergnathic relation and shape of the dental arches served as the basis. It was followed by a reconstruction of the defective alveolus using autologous cancellous bone grafts, harvested from an iliac crest. Dental implants were inserted 12-15 weeks after the transplantation and subsequently a prosthetic component was applied with a time delay of at least 2 months. After the orthodontic preparation, reconstruction of the alveolus has so far been performed in 38 patients. Their age was at least 14 years, i.e. the age when growth of the orofacial region was finalised or already complete. The crucial tasks at this stage are to form a stable, three-dimensional voluminous alveolar crest, and to cover the grafts with a sufficient amount of quality soft tissue. We needed an average amount of 3.7 ccm of cancellous bone graft for the reconstruction. This amount can be harvested only from an enchondral bone. For soft tissue shell the mucoperiosteal shift of flap from cleft segment was used. In more serious cases contralateral or even bilateral shift was performed. The relief of tissue tension was performed by double cut-back. Using the approach described we attained a 84.2% success rate. Our results and experience derived within this project show that the success rate of this procedure depends on the continuous flow of the alveolar arch with a good intergnathic relation, with a length of defect between crowns of border teeth of at least 8 mm. The original osseous walls of the defect must definitely be of suitable height. On-lay augmentation does not work in these cases. A subsequent pitfall lies in resorption of transplanted bone, which may be reduced due to an early load by a dental implant. During the three months after the reconstruction a spongy osseous graft matures enough to ensure the primary stability of a fixture.
Keywords: finanční podpora výzkumu jako téma; rozštěp patra; transplantace kostí; Plastic Surgery Procedures; maxila; Bone Transplantation; Research Support as Topic; Humans; lidé; Dental Implants; zubní implantáty; Adolescent; zákroky plastické chirurgie; mladiství; Maxilla; Cleft Palate